Pengembangan Materi Ajar Mata Kuliah Kewirausahaan Program Studi Magister Pendidikan Seni Rupa PPS UNM - Alimuddin Alimuddin; Pangerang Paita Yunus (Seminar Nasional LP2M UNM, 2022)
Abstract, Entrepreneurship courses taught in the PPs UNM Fine Arts Education Masters Study Program. The competency demands that are expected of students are to have entrepreneurial sensitivity, insight into entrepreneurial knowledge, have the ability to uncover their potential and be able to create businesses in their scientific fields. This study aims to (1) obtain competency formulations or learning outcomes expressed in the form of lesson plans, (2) establish a systematic framework for Teaching Materials, (3) arrange teaching materials with good validity. Due to the type of development research, the development procedure adapts that developed by Borg & Gall which consists of ten steps, but in practice only three stages can be carried out, namely from 1) preliminary study and data/information collection, 2) planning, 3) developing a draft initial and validation test or review by the validator. The result of this research is to give birth to the output of the Teaching Materials Book as a learning tool whose contents include the formulation of competency achievement for the course, the contents of the teaching material, and bills of course assignments. This Teaching Materials Book has fulfilled the eligibility criteria with an average validity test score = 4.69 (very good category) by the material expert and media expert validators. In order for this research to be more perfect and complete, it is recommended to carry out further research trials in fulfilling the material as having a feasibility level of effectiveness and practicality. Keywords: Development, Teaching Materials, Entrepreneurship